1994
DOI: 10.1002/arch.940250203
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetics of [3H]‐dihydroazadirachtin in the variegated cutworm Peridroma saucia

Abstract: The excretion, retention, and tissue distribution of [3H]-dihydroazadirachtin was investigated in the variegated cutworm, Peridroma saucia (Noctuidae). The candidate compound was rapidly cleared from the hemolymph following either oral exposure or topical administration, with maximum concentrations at 6 h post-treatment and peak appearance of label in the frass at 12 h. However, approximately 45 and 55% of the labelled material was retained in the body at 72 h in respective treatments. Major depots for retaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Thus, this effect is unequivocally independent of its antifeedant properties. However, when S. litura sixth instars were force-fed with leaf discs within 6 h, to consume about 1.2 #g of azadirachtin as described earlier (Koul et al, 1994), growth regulatory effects were observed. We used this procedure in addition to topical and injection methods to demonstrate the reduction in the activity of midgut trypsin, which is a primary protease in the gut in many lepidopteran genera (Broadway & Duffey, 1988), and to show whether the mode of application imparts any variation in this enzyme reduction.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Thus, this effect is unequivocally independent of its antifeedant properties. However, when S. litura sixth instars were force-fed with leaf discs within 6 h, to consume about 1.2 #g of azadirachtin as described earlier (Koul et al, 1994), growth regulatory effects were observed. We used this procedure in addition to topical and injection methods to demonstrate the reduction in the activity of midgut trypsin, which is a primary protease in the gut in many lepidopteran genera (Broadway & Duffey, 1988), and to show whether the mode of application imparts any variation in this enzyme reduction.…”
Section: Discussionmentioning
confidence: 89%
“…However, after injection and topical application this activity was reduced to 34% and 37.5% respectively. Toxicokinetic studies of azadirachtin have clearly shown that retention of this allelochemical in the tissues varies with the mode of application (Koul et al, 1994); thus a possible variation in tryptic activity as well. Our findings indicate that decrease in tryptic activity may not be due to direct inhibition of the enzyme and has already been demonstrated in Manduca sexta (Timmins & Reynolds, 1992), So the possibility of the direct action on enzyme secreting cells of the midgut wall or the mechanism which controls trypsin secretion (may be hormonal) is highly probable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations